Case Report: Pelvic Congestion Syndrome as an Unusual Etiology for Chronic Hip Pain in 2 Active, Middle-Age Women. (March 2014) - Shelkey, Julia; Huang, Christina; Karpa, Kelly; Singh, Harjit; Silvis, Matthew
Context: The past 2 decades have shown a dramatic increase in the number of pelvic and hip injuries in female athletes. Accurate diagnosis of hip pain in active women has proven to be a challenge, as there is an extensive differential including both musculoskeletal and visceral problems. While the incidence of pelvic congestion syndrome (PCS) is not known, this condition may manifest as chronic hip pain in this patient population. Evidence Acquisition: A PubMed search was undertaken for articles published in English from 1980 to 2012. Additional references were accrued from reference lists of research articles. Study Design: Case series. Level of Evidence: Level 3. Results: Diagnosis was established using magnetic resonance imaging. Both women were evaluated and treated by interventional radiology with gonadal vein embolization. Initial evaluation and subsequent follow-up was completed in the Sports Medicine Clinic to monitor chronic hip pain symptoms. Both patients experienced significant alleviation of chronic hip pain symptoms within several months after gonadal vein embolization, allowing for a return to the previous level of activity. Conclusion: Although PCS most commonly presents as pelvic pain, it is important to consider this condition in athletes with persistent hip pain. PCS may also present with the primary symptom of hip pain as in the 2 case reports described. With more awareness of this condition and appropriate diagnosis, PCS as an unusual etiology of chronic hip pain may be effectively treated with gonadal vein embolization.